2022
DOI: 10.3389/fphar.2022.920411
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development of Natural Product Tanshinone I: Pharmacology, Total Synthesis, and Structure Modifications

Abstract: Salvia miltiorrhiza (S. miltiorrhiza), which has been used for thousands of years to treat cardiovascular diseases, is a well-known Chinese medicinal plant. The fat-soluble tanshinones in S. miltiorrhiza are important biologically active ingredients including tanshinone I, tanshinone IIA, dihydrotanshinone, and cryptotanshinone. Tanshinone I, a natural diterpenoid quinone compound widely used in traditional Chinese medicine, has a wide range of biological effects including anti-cancer, antioxidant, neuroprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Lithospermic acid B exerted anti-steatotic and anti-inflammatory effects against alcoholic liver injury by inducing SIRT1-mediated inhibition of CRP and ChREBP expression [ 59 ] and it could also alleviate acute ethanol-induced hepatocyte apoptosis through SIRT1-mediated deacetylation of p53 pathway [ 34 ]. Tanshinone I, dihydromyricetin, and chlorogenic acid have been reported to have certain preventive or therapeutic effects on alcoholic liver disease, nonalcoholic liver disease or inflammatory diseases [ 29 , 42 , 50 ]. Chlorogenic acid (of 169 μg/g in BGXJW) and dihydromyricetin (of 100 μg/g in BGXJW) protect liver function via altering lipid metabolism and enhancing alcohol metabolism, [ 5 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lithospermic acid B exerted anti-steatotic and anti-inflammatory effects against alcoholic liver injury by inducing SIRT1-mediated inhibition of CRP and ChREBP expression [ 59 ] and it could also alleviate acute ethanol-induced hepatocyte apoptosis through SIRT1-mediated deacetylation of p53 pathway [ 34 ]. Tanshinone I, dihydromyricetin, and chlorogenic acid have been reported to have certain preventive or therapeutic effects on alcoholic liver disease, nonalcoholic liver disease or inflammatory diseases [ 29 , 42 , 50 ]. Chlorogenic acid (of 169 μg/g in BGXJW) and dihydromyricetin (of 100 μg/g in BGXJW) protect liver function via altering lipid metabolism and enhancing alcohol metabolism, [ 5 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been numerous studies on the use of Tan IIA in gastric cancer, 8,14 research on Tan I in this context is limited, with only one article discussing its role in inducing apoptosis in gastric cancer. 27 However, it is worth noting that the cell lines used in the experiment (BGC823 and SGC7901) were suspected to be contaminated with HeLa cells, which may jeopardize the reliability of the conclusion. 23 Therefore, it is essential to further investigate the role of Tan I in gastric cancer and elucidate its underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is currently no specific inhibitor of PLA2G2A for the clinical treatment of cancer, tanshinone I has been reported to inhibit PLA2G2A and could disrupt cellular PUFA metabolism for the synthesis of eicosanoids [ 23 ]. This compound has been shown to exert antitumor effects by inducing apoptosis through the generation of reactive oxygen species in human hepatocellular carcinoma [ 34 ] and endometrial cancer cells [ 35 ], and has been shown to inhibit cell proliferation by blocking the cell cycle and autophagy in various tumor cell models [ 36 ]. Recently, tanshinone I was also proposed as an inhibitor of the enhancer of zeste homolog 2 (EZH2) [ 37 ], suggesting that tanshinone I might be a multi-targeting compound, and its biological effect is likely the combined results of its actions on multiple targets.…”
Section: Discussionmentioning
confidence: 99%